Heterogeneous middle-class and disparate educational advantage: parental investment in their children's schooling in Dehradun, India. Issue 1 (2nd January 2020) - Gupta, Achala
Abstract: The heterogeneity of the contemporary Indian middle-class has been discussed widely. However, the effect of its internal differences on the distribution of educational resources needs to be examined systematically. Drawing upon in-depth interviews with parents in 53 middle-class families in Dehradun, India, this paper explores three aspects of the home-school relationship: how socioeconomic transformations shape parents' aspirations for their children's future, educational decisions parents make to realise those aspirations, and mothers' engagement in their children's everyday schooling. The tripartite analysis reveals that despite sharing common educational goals and strategies with the population in general, middle-class families in India use their class privilege to gain valuable educational resources. The paper argues that the discrepancy in the mobilisation of accumulated resources in the heterogeneous middle-class results in disparate educational advantages across families. It critiques the binary construction of social classes when explaining the processes of social reproduction in contemporary Indian society.